Table Installments Finance Sharia of Motor Vehicle Using Proportional, Annuity, and Effective Rate Method - Cahyandari, Rini; Hasanah, Faridatul (International Journal of Mathematics, Statistics, and Computing, 2023)
One of the products offered by sharia banks is financing. In this financing, Islamic banks usually take profits in the form of margin or it can also be done by profit sharing. The base profit rate model was introduced to determine margins in Islamic bank financing. The margin generated using the base profit rate model is only in the form of a percentage. Therefore, follow-up was carried out by forming a sharia financing installment table to make it easier to see profits in nominal form. The methods used in making this installment table are the proportional method, annuity method and effective rate method. From research conducted in the case of sharia motor vehicle financing with a term of 1 year, a margin of 66.61785% was obtained and the profit based on the calculation results of the proportional method, annuity method and effective rate method was respectively IDR. 9,992,677.20,- , Rp. 5,945,097.50,-, and Rp. 5,412,700.31. So it can be concluded that the effective rate method takes the smallest profits, then followed by the annuity method and finally the proportional method which takes profits that tend to be larger.